STUDENTS' ATTITUDES TOWARD SUSTAINABILITY IN THEIR DESIGN PERSPECTIVES - Kushwaha, Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In 2002, the United Nations designated the years 2004-2015 as the "Decade of Education for Sustainable Development," with the purpose of integrating education into social development that adheres to sustainable principles. The deficiency of attachment to one's garments and their disposal after a single usage have become the standard of the day. The fashion business adds to the burden on Earth's limited resources. Global warming has been progressively growing; it reached 1.2°C in 2022, and there is a strong risk of topping 1.5°C within ten years. In 2022, global carbon dioxide (CO2) emissions reached a new high of 36.8 giga tones. The fashion sector accounts for 10% of all global carbon dioxide emissions. This industry accounts for 20% of industrial wastewater contamination. The Sustainable Development Goal (SDG) Index assesses 193 nations' progress toward sustainable goals. The Sustainable Development Goals are far off-track midway through the 2030 Agenda. The globe is also far from meeting Sustainable Development Goal 13 and the Paris Agreement's climate goals. This study seeks to investigate the attitudes and understanding of design students aged 18 to 25 regarding sustainability. A sustainability survey was done utilizing a questionnaire among 110 first-year students and 110 fourth-year students. A questionnaire survey was carried out using Google Forms. This study exposed that, despite spending three years more in college than first-year students, fourth-year students do not have a significantly greater understanding of sustainability.